The functional effect of 3D-printing individualized orthosis for patients with peripheral nerve injuries: Three case reports. Issue 16 (April 2020) - Chae, Dong-Sik; Kim, Da-Ham; Kang, Kyung-Yil; Kim, Doo-Young; Park, Si-Woon; Park, Sung-Jun; Kim, Jae-Hyung
Abstract: Rationale: In the medical field, the use of 3-dimensional (3D) printing is increasing explosively and it is especially widespread in the clinical application of fabricating orthosis. Advantages of 3D-printed orthosis compared to conventional ones include its lower cost, easier modification, and faster fabrication. The 3D-printing technique makes it possible for physicians to easily create individual-tailored products. Recently, many kinds of orthosis through 3D printing have been studied and used. The knee orthosis, ankle-foot orthosis, wrist orthosis, hand orthosis, and foot orthotics are examples used in the rehabilitation fields of orthotics. We reported 3 cases of 3D-printed orthoses in patients with peripheral nerve injuries. Patients concerns: In spite of the rapid development of the clinical use of 3D printing, to our knowledge, its application to patients with peripheral nerve injuries has not yet been reported. Two patients suffered from upper limb problems and 1 patient had a foot drop associated with peripheral nerve injury. Diagnosis: Three patients diagnosed with median neuropathy, ulnar neuropathy, and right lower lumbar radiculopathy, respectively, by electromyography. Interventions: Herein we present 3 case reports of patients with peripheral nerve injuries whose orthotic needs were fulfilled with the application of 3D-printed wrist orthosis and ankle-foot orthosis. Outcomes: For hand function evaluation, we assessed the Jebsen–Taylor hand function test. Grasp and pinch powers were assessed by a hand dynamometer before and after orthosis application. For lower limb functional evaluation, we used a 6-minute walking test and modified Emory Functional Ambulation Profile for ambulatory function. Lessons: The 3D-printed orthosis could help functional improvement in patients with peripheral nerve injuries.